The Impact of Ramadan Fasting on Oral Health Biomarkers Linked to Dental Caries - Mohammad, Baraa Sadiq; Taha , Ghada Ibrahim (AL-Kindy College Medical Journal, 2025)
Background: Dental caries is a prevalent oral health problem, with saliva playing a pivotal role in maintaining oral hygiene. Fasting during Ramadan offers a unique scenario where changes in dietary habits, salivary flow, and pH levels might affect dental health markers.Aim of the Study: This study aims to understand the implications of Ramadan fasting on various dental biomarkers, such as pH, Salivary Flow Rate (SFR), Glucosyltransferase (GTF), and Interleukin-8 (IL-8) levels in individuals with dental caries.Subjects and Methods: A longitudinal observational study was conducted on 40 participants with dental caries, evenly distributed between males and females, aged between 20-25 years, during and after Ramadan. Clinical data and samples were collected at the College of Dentistry/University of Baghdad, Iraq, and the Specialized Dental Center/Al-Sadr City. Participants were assessed for periodontal parameters using the Plaque Index (PLI) and the GI. Salivary samples were collected, and pH level and salivary flow rate were determined. Enzyme-linked immunosorbent Assay was utilized to detect Glucosyltransferase and interleukin-8 levels in saliva samples.Results: There was a non-significant rise in pH during fasting (6.09±0.77) compared to after fasting (5.80±0.78). The SFR showed a non-significant decline during fasting (0.74±0.35) when compared to after-fasting (0.88±0.43). Plaque and gingival indices exhibited non-significant changes between the two groups. Notably, GTF levels significantly decreased during fasting, while IL-8 levels showed a marked reduction during fasting (218.83±23.55 ng/L) compared to after fasting (389.07±35.93 ng/L).Conclusions: This study found that fasting throughout Ramadan has an impact on biomarkers related to dental health. Levels of GTF and IL-8 exhibited considerable changes, whereas pH and SFR remained unchanged. Reducing GTF levels may lead to a decrease in the formation of dental plaque and tooth decay. Decreased levels of IL-8 may suggest a decrease in inflammatory activity, which in turn lowers the risk of periodontal disease.